EFEKTIFITAS TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS VII PUTRI SMP ISLAM TERPADU JEMBER - Afifah Binti Khairul Hadi; Imaratul Ulwiyah; Weni Kurnia Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning independence is a learning program arrangement made by the organization in such a way that each student can choose and even determine their own learning materials and progress. Meanwhile, not all students are able to learn independently on their own accord without the help of others. This study aims to test the effectiveness of self-management techniques to improve learning independence of female students in grade VII of SMPIT Al Ghozali Jember. The research method used is an experiment with pretest-posttest one group design. The subjects of this study were 8 female students in grade VII who had low learning independence. Data analysis was carried out using the non-parametric Wiloxon sign rank test to measure the comparative hypothesis between two samples that correlate with ordinal data. The results of the study from the self-management technique were significantly effective in improving learning independence in students. Based on these results, students are already at the stage of being able to learn independently, but considering that learning independence is very important, it is necessary for students to always increase their priorities.